Harnessing Loose Part Media for Cognitive Development: Evaluating Its Effects on Early Mathematics Play Activities in Early Childhood Education - Mei Purnama Nasution; Darliana Sormin; Jumaita Nopriani Lubis; Sri Wahyuni; Adek Kholijah Siregar; Abdulroman Mahir (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
The implementation of Loose Part media has proven to enhance various aspects of children's development, particularly in cognitive development. This study aims to evaluate the impact of implementing Loose Part media in early mathematics play activities on the cognitive development of early childhood at 'Aisyiyah Bustanul Athfal (ABA) Simangambat Mandailing Natal Kindergarten. The research adopts the Classroom Action Research (CAR) method, utilizing a quantitative approach to measure the success rate of the children and a qualitative approach to observe advanced development and decision-making. Loose Part media is applied to stimulate the cognitive development of early childhood through early mathematics play activities. The research population involves early childhood subjects in Group B, aged 5-6 years, at 'Aisyiyah Bustanul Athfal (ABA) Simangambat Mandailing Natal Kindergarten, totaling 22 children. The research findings indicate that the implementation of Loose Part media significantly improves the cognitive development of early childhood. Before the intervention, the average score was 30%, which increased to 62.68% after Cycle I and reached 85.20% after Cycle II. Consequently, learning through Loose Part media in play activities proves to be an effective choice for enhancing the cognitive development of early childhood. The interpretation of the research results reveals a significant enhancement in children's cognitive abilities through interaction with Loose Part media. The substantial improvement, reflected in the average score progression from Cycle I to Cycle II (85.20%), indicates the positive contribution of Loose Part media in early mathematics play activities to the cognitive development of early childhood.